OP0093 FREQUENCIES AND PREDICTORS OF THE LUPUS LOW DISEASE ACTIVITY STATE AND REMISSION IN TREATMENT-NAÏVE PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS – A REAL-WORLD COHORT STUDY. (2nd June 2020) - Gao, D.; Hao, Y.; Mu, L.; Xie, W.; Sun, X.; Fan, Y.; Ji, L.; Zhang, Z.
Abstract : Background: After the introduction of treat-to-target strategy in systemic lupus erythematosus (SLE), Lupus Low Disease Activity State (LLDAS) and definitions of remission in SLE (DORIS) were developed and validated. Several studies had demonstrated that the achievement and maintenance of LLDAS or DORIS was associated with good prognosis. Objectives: To evaluate the attainability of LLDAS and DORIS in a treatment-naïve cohort of SLE. Methods: LDAS5 was defined as LLDAS with a prednisone dose ≤5 mg/d. There were 4 definitions in DORIS: clinical remission on treatment (RONT), complete RONT, clinical remission off treatment (ROFT) and complete ROFT. The treatment-naïve patients from Peking University First Hospital SLE cohort were enrolled. The time to each state and their annual cumulative probabilities were estimated by Kaplan-Meier approach. The frequencies of patients who achieved each component of LLDAS or DORIS during follow-up were determined. Results: A total of 218 treatment-naïve patients were included, with a median follow-up of 4.48 years. Respectively, 190 (87.2%), 160 (73.4%), 148 (67.9%), 94 (43.1%), 23 (10.6%) and 18 (8.3%) patients achieved LLDAS, LLDAS5, clinical RONT, complete RONT, clinical ROFT and complete ROFT at least once during the follow-up time. The median time to LLDAS, LLDAS5, clinical RONT and complete RONT were 1.4, 2.3, 2.6 and 4.7 years, respectively. Conclusion: Our data confirmed that LLDAS is an attainable early treatment target for SLE. Though with more difficulty, RONT can be achieved in two-thirds of our patients. ROFT may not be an ideal treatment target at present as it is only attained in few patients. References: [1]Franklyn, K. et al. Ann Rheum Dis. 2016 Sep;75(9):1615-21. [2]van Vollenhoven, R. et al. Ann Rheum Dis. 2017 Mar;76(3):554-561. Disclosure of Interests: None declared